Giving and Receiving Critical Feedback in Higher Education - Lamichhane, Purna Bahadur (Cognition, 2019)
This research article deals with feedback practices given by the teachers and received by the students in English as a foreign language classroom. It also highlights the attitudes and feelings of teachers towards the oral feedback. This study gives some insights into the role of oral feedback in the EFL classroom and effective feedback strategies to EFL teachers, students, researchers and policy makers. It paves the way for effective classroom interactions between teachers and students. The teachers had different views on the issues related to the use of feedback strategies in EFL classrooms. Although the teachers have understood the importance of oral feedback and been familiar with some common strategies of using oral feedback contextually, some teachers are found to have neglected the use of giving oral feedback in language teaching From this study, I found that teachers need to learn a variety of interactive activities for giving oral feedback in practice and students need some instruction for receiving it.